Talent Management in The Generation Z Era : Challenges and Retention Strategies in Modern Organizations - Deka Meuthia Novari; Ricky Febrian (Maneggio, 2026)
The increasing dominance of Generation Z in the global workforce presents significant challenges and opportunities for modern organizations, particularly in the design of effective talent management and retention strategies. This study aims to analyze how talent management systems can be strategically restructured to address the distinctive characteristics of Generation Z and enhance long-term employee retention. A qualitative approach using a Systematic Literature Review method was employed, examining recent peer-reviewed studies focusing on Generation Z workforce behavior, organizational challenges, and retention practices. Data were analyzed through thematic synthesis to identify recurring strategic dimensions within contemporary talent management systems. findings reveal that retention in the Generation Z era depends on an integrated and value-aligned talent management framework encompassing digital recruitment, strategic onboarding, structured and personalized career development, inclusive and purpose-driven culture, flexible work arrangements, technological workplace infrastructure, and comprehensive total reward systems. The discussion highlights that retention outcomes improve when organizational systems align with Generation Z’s expectations for flexibility, meaningful work, growth opportunities, and continuous feedback. In conclusion, effective retention of Generation Z requires systemic alignment across the entire talent lifecycle rather than isolated human resource interventions, ensuring sustainable engagement and organizational competitiveness in a rapidly evolving demographic landscape.